THE DICHOTOMY BETWEEN SIGNAL AND CONTENT AS BASIS OF BROADCAST COPYRIGHT: A KENYAN AND SOUTH AFRICAN PERSPECTIVE - Hezekiel Oira; Lonias Ndlovu (Obiter, 2018)
The concept of broadcast copyright is one of the most controversial and non-felicitous subjects, both at national and transnational levels. Most municipal copyright laws and relevant international instruments merely provide that broadcasting organizations shall enjoy protection over their broadcasts and programme-carrying signals. Some of those international instruments include The Rome Convention for the Protection of Performers, Producers of Phonograms and Broadcasting Organizations of 1961 (hereinafter “the Rome Convention”). Article 13 thereof grants specific exclusive rights against certain activities in relation to the broadcasts of broadcasting organizations. Additionally, Article 1 of the Rome Convention guarantees that its exercise and implementation shall leave intact and in no way affect the protection of copyright in literary and artistic works. The Agreement on Trade-Related Aspects of Intellectual Property Rights (hereinafter “the TRIPs Agreement”) of 1994 follows the model of the Rome Convention, and under Article 14 (3) grants broadcasting organizations the same neighbouring rights as the latter does. In both instruments, the object of protection in a broadcast or broadcasts was never defined. The Convention Relating to the Distribution of Programme-Carrying Signals Transmitted by Satellite (hereinafter “the Satellite Convention”) of 1974 does not grant broadcasting organizations any specific right but obliges Contracting Parties to prevent unauthorized distribution on or from their territories of any programme-carrying signal by any distributor for whom the signal emitted to or passing through the satellite is not intended. The protection conferred upon the broadcasting organizations under the above international instruments are replicated in the copyright laws of Kenya and South Africa without clarifying upon the property and the scope of protection of a broadcast. The failure to specifically define the subject matter of protection in broadcast copyright as well as its outer boundaries forms the genesis of the current controversy. Amid this controversy, this article examines two emerging global approaches around which broadcast copyright revolves, namely the content or rights-based approach, and the signal-based approach. Drawing from the two approaches, the article examines the extent to which they apply to Kenya and South Africa.